Analisis Ketersediaan Kedelai Pada Koperasi Karya Mulya desa Sepande Kabupaten Sidoarjo - Layllindra, Fasya Arifatin; Soedarto, Teguh; Syah, Mirza Andrian (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
Karya Mulya Cooperative is a cooperative that provides soybean raw materials for tofu and tempeh craftspeople in Sepande Village, Sidoarjo Regency. This study aims to determine the optimal amount of soybean raw material inventory that should be carried out by Koperasi Karya Mulya, the optimal frequency of purchasing raw materials, the right time to purchase raw materials, the optimal total ordering cost made for the procurement of soybean raw materials, and the implementation of an effective and efficient warehouse management system. This type of research is descriptive quantitative by describing the control of raw material inventory carried out by cooperatives through data obtained and then analyzed. Data analysis used includes Economic Order Quantity (EOQ), Reorder Point (ROP), Safety Stock (SS), and FIFO methods. Based on the results of the analysis using the EOQ method, Koperasi Karya Mulya should order an optimal raw material frequency of 6,459.14 tons with a purchase frequency of 210 times, ROP 7.009,25 Â tons, Safety Stock of 5.857,81 tons and total storage costs of Rp427,272,734.03.